Augmentation of NVP-BEZ235's anticancer activity against human lung cancer cells by blockage of autophagy - Xu, Cheng-Xiong (Landes Bioscience, 2011)
Autophagy is a cellular lysosomal degradation pathway essential for regulation of cell survival and death to maintain homeostasis. This process is negatively regulated by mammalian target of rapamycin (mTOR) signaling and often counteracts efficacy of certain cancer therapeutic agents. NVP-BEZ235 (BEZ235) is a novel, orally bioavailable dual PI3K/mTOR inhibitor that has exhibited promising activity against non-small cell lung cancer (NSCLC) in preclinical models. The current study focuses on evaluating the role of BEZ235 in regulating autophagy. BEZ235 was effective in inhibiting the growth of NSCLC cells including induction of apoptosis. It also potently induced the expression of type-II LC3, indicating induction of autophagy. When BEZ235 was used in combination with the lysosomal or autophagic inhibitor chloroquine (CQ), enhanced inhibitory effects on monolayer growth and colony formation of NSCLC cells was observed. In addition, enhanced induction of apoptosis was also detected in cells exposed to the combination of BEZ235 and CQ. Moreover, the combination of BEZ235 and CQ was more effective than each single agent alone in inhibiting the growth of NSCLC xenografts in nude mice. Thus, induction of autophagy by BEZ235 appears to be a survival mechanism that may counteract its anticancer effects. Based on these, we suggest a strategy to enhance BEZ235's anticancer efficacy by blockade of autophagy.